Kegiatan Penapisan Kesehatan Kulit Wajah dan Kerusakan Kulit Akibat Paparan Sinar Matahari pada Kelompok Lanjut Usia di St. Anna - Tan, Sukmawati Tansil; Gunaidi, Farell Christian; Wijaya, Dean Ascha; Alifia, Tosya Putri; Syarifah, Andini Ghina (Universitas 17 Agustus 1945 Semarang, 2024)
Ultraviolet (UV) radiation, especially UVB and UVA, plays an important role in the pathogenesis of skin damage. Excessive sun exposure causes various skin problems, such as burning, dehydration, and premature aging, and increases the risk of skin cancer. Precautions such as using sunscreen, protective clothing, and avoiding peak UV exposure times are essential. Using the PDCA (Plan-Do-Check-Act) cycle, we carry out facial skin health checks, including education about sun protection, identification of skin problems, and follow-up interventions. 33 participants (11 men and 22 women) participated in this activity. It was found that the average wrinkle, roughness, moist, and UV damage were 17%, 20%, 46%, and 22.18% respectively. Early counseling and screening is essential to increase awareness, change behavior, and prevent skin problems, ultimately improving skin health and improving quality of life.